A propósito de Bauman y los retos de la educación en la modernidad líquida Cavilaciones sobre el futuro de la enseñanza de la Historia - Betancur Cruz, Luis Bernardo (Universidad Santiago de Cali, 2017)
The purpose of this paper is to open the discussion about the new pedagogical and social scenarios facing the teaching of history, taking as a point of reflec-tion the notes made by Zigmut Bauman in his text the challenges of education in liquid modernity. The center of the concern for the teaching of history in the country passes for at least two moments, the first, the kind of history that is taught and how it should be taught, second, the attempt by some historians to recover history As an independent subject in the area of Social Sciences; Nevertheless it is equally important to begin to question questions that have not had much place within the reflection of the didactics of the History in our context who are the scholars of today? What are their realities and interests? What is the relation and pertinence that the learners establish with the trans-mitted knowledge, especially historical? How is history still taught? And what are the most common didactic practices?